2017
DOI: 10.2147/ott.s137726
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA, TINCR, functions as a competing endogenous RNA to regulate PDK1 expression by sponging miR-375 in gastric cancer

Abstract: BackgroundAccumulating evidence indicates that the long noncoding RNA, TINCR, plays a critical role in cancer progression and metastasis. However, the overall biological role and mechanisms of TINCR that were involved in human gastric cancer (GC) progression remain largely unknown.MethodsTINCR expression was measured in 56 paired tumor and adjacent nontumor tissue samples by real-time polymerase chain reaction (PCR). Insights of the mechanism of competitive endogenous RNAs (ceRNAs) were gained from bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 21 publications
2
46
0
Order By: Relevance
“…It has been reported that H19 is upregulated in tumors including colorectal cancer, breast cancer, and bladder cancer (Raveh, Matouk, Gilon, & Hochberg, ). For instance, overexpression of H19 indicates unfavorable prognosis in colorectal cancer patients and can increase colon cancer cell proliferation (Chen, Liu, et al, ). H19‐derived miR‐675 can promote breast cancer progression via inhibiting c‐Cbl and Cbl‐b (Vennin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that H19 is upregulated in tumors including colorectal cancer, breast cancer, and bladder cancer (Raveh, Matouk, Gilon, & Hochberg, ). For instance, overexpression of H19 indicates unfavorable prognosis in colorectal cancer patients and can increase colon cancer cell proliferation (Chen, Liu, et al, ). H19‐derived miR‐675 can promote breast cancer progression via inhibiting c‐Cbl and Cbl‐b (Vennin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A novel regulatory circuitry has been recently identified that lncRNAs could function as a "sponge" to crosstalk with miRNAs (35). For example, lncRNA TINCR functions as a ceRNA to regulate PDK1 expression by sponging miR-375 in GC, in which tumor growth and invasion were suppressed with downregulated lncRNA TINCR and PDK1 (36). In the sepsis-induced acute kidney injury patients, the repression of lncRNA NEAT1 retarded the lipopolysaccharide-induced injury via overexpression of miR-204, as a result of inactivation of the NF-κB pathway, a potential pro-inflammatory pathway (37).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are extensively targeted by miRNAs through 3′ UTR or 5′UTR, meaning that they could serve as ceRNAs, the lncRNA as ceRNA were associated with cellular biological process and also serve important roles in tumorigenesis . Recent published studies confirmed the ceRNA theory involved in the progression of various types of cancer . These studies aimed at some genes including mRNA, miRNA, and lncRNA associated with the cancer and confirmed that some of genes serve important roles in treatment and prognosis.…”
Section: Introductionmentioning
confidence: 89%
“…11 Recent published studies confirmed the ceRNA theory involved in the progression of various types of cancer. [12][13][14][15] These studies aimed at some genes including mRNA, miRNA, and lncRNA associated with the cancer and confirmed that some of genes serve important roles in treatment and prognosis. With the development of experimental studies and techniques for lncRNA discovery, lncRNA-associated ceRNA networks have been constructed and analyzed in colorectal cancer, gastric cancer, and osteosarcoma.…”
Section: Introductionmentioning
confidence: 98%